Mental health of public safety personnel: Developing a model of operational, organizational, and personal factors in public safety organizations - Edgelow, Megan; Fecica, Agnieszka; Kohlen, Caroline; Tandal, Kirandeep (Frontiers in Public Health, 2023)
The work of public safety personnel (PSP) such as police officers, firefighters, correctional officers, and paramedics, as well as other PSP, makes them vulnerable to psychological injuries, which can have profound impacts on their families and the communities they serve (1). A multitude of complex operational, organizational and personal factors contribute to the mental health of PSP; however, to date the approach of the research community has been largely to explore the impacts of these factors separately or within single PSP professions (2). To date, PSP employers have predominantly focused on addressing the personal aspects of PSP mental health through resiliency and stress management interventions (3). However, the increasing number of psychological injuries among PSPs and the compounding stressors of the COVID-19 pandemic demonstrate a need for a new approach to the study of PSP mental health (1, 2, 4, 5). The following paper discusses the importance of adopting a broader conceptual approach to the study of PSP mental health and proposes a novel model that highlights the need to consider the combined impacts of operational, organizational, and personal factors on PSP mental health. The TRi-Operational-Organizational-Personal Factor Model (TROOP) depicts these key factors as three large pieces of a larger puzzle that is PSP mental health. The TROOP gives working language for public safety organizations, leaders, and researchers to broadly consider the mental health impacts of public safety work.